The effects of poor management practices in Yemeni universities on job dissatisfaction and brain drain - ‪Sukainah Hasan Saleh Al-Hebshi‬‏; Antar Fuad Ali Alharazi; Aminullah Abdulrasheed Abdullah; Siti Zubaidah Othman (Universiti Sains Islam Malaysia, 2025)
‘Abqari Journal. Volume 32 issue 1 Page (25–36)